The Development of Islamic Legal Studies in the Islamic World in the Modern Period - Mastawiyah; Mila Erliana; Meilinda Salsabila (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2025)
This research examines the development of Islamic legal studies in modern times, where Islamic studies have deep roots, with a history and development that reflects social, political, and intellectual dynamics in both the Islamic world and the West. Seeing from these problems, the development of Islamic legal studies is not only seen from the modern period, but also must be seen from the past. The research method is a normative method with a critical discourse analysis approach. The results of research on Islamic studies have developed significantly since the seventh century, reflecting the interaction between the Islamic world and Western intellectual traditions. In the Islamic world, science began with the writing of the Qur'an and hadith, developed through Islamic boarding schools and madrasas, and produced important works in the fields of theology, law, and philosophy. Western interest in Islam grew in the Middle Ages, especially through the translation of works by Islamic scholars that enriched European thought. In the 19th and 20th centuries, Islamic studies became a formal academic discipline, often influenced by critical Orientalist perspectives. Today, Islamic studies is interdisciplinary and focuses on contemporary issues such as human rights, gender, and modern relations with Islam. The interaction between the Islamic world and the West continues to deepen our understanding of Islam, making it a dynamic and relevant field in a global context.